An assessment of leadership development needs of school leaders for the 4.0 - Letuma, Ntsebeng R.; Awodiji, Omotayo Adewale; Naicker, Suraiya Rathankoomar (Journal of Management and Business Education, 2023)
As a result of the fourth industrial revolution (4.0), school leaders need to consider if their existing abilities and competences satisfy future-fit leaders' requirements. This study evaluated the leadership development (LD) needs of school leaders in the 4.0 era. A survey design was used. Cluster sampling technique was adopted to randomly select a sample of 505 school management teams (SMT). The study found that school leaders require LD that will enable them to become proficient with technology applications, technology hardware, and emerging 4.0 technologies. Leaders must be trained in the use of cutting-edge 4.0 technology, applications, and technology. With regard to gender there was no significant difference in technological knowledge but LD needs in the areas of agility, information management, problem solving, communication and collaboration will benefit female leaders. This study contributes significantly to the basic school leadership development in Africa by addressing 4.0 training needs. This includes the understanding of school leaders' training needs, as well as the way in which gender influences training needs. It is recommended that the education department develop training programmes and implement mechanisms such as professional learning communities, mentoring and coaching to enhance school leadership competencies for the 4.0.